Evaluation of temperature on survival, metabolism, and morphological changes in Palm ruff (Seriolella violacea) larvae - Begoña Cárcamo; Boris Dewitte; Alexandra Parouffe; Aurélien Paulmier; Véronique Garçon; Laura Ramajo; Sebastián San Martín; Juan Varas; Marcia Oliva; Edison Serrano; Nieves Sandoval; Katherine Jeno; et al. (Aquaculture, 2026)

First Report of Tenacibaculum dicentrarchi in Diseased Palm Ruff ( Seriolella violacea , Guichenot 1848) From an Experimental Culture in Chile - Ruben Avendaño‐Herrera; Henry Araya‐León; Marcia Oliva; Rute Irgang; Edison Serrano (Journal of Fish Diseases, 2026)
Palm ruff ( Seriolella violacea , Guichenot 1848) has been identified as a promising candidate for aquaculture in northern Chile. During the winter of 2023, an outbreak of an external infectious disease affected 3740 juvenile Palm ruff at the Marine Fish Farming Laboratory of the Universidad Católica del Norte. The macroscopic signs, particularly external ulcers, were consistent with tenacibaculosis. Microbiological, genomic and typing analyses were conducted to determine the cause of fish mortality. Sixteen isolates were recovered from four moribund fish, primarily from external lesions organs such as the mouth ( n = 4), skin lesions ( n = 4) and gill ( n = 1). All isolates exhibited phenotypic traits characteristic of Tenacibaculum dicentrarchi : Gram‐negative, motile rods, positive catalase and oxidase activity, Congo red absorption and an absence of flexirubin pigment. PCR analysis confirmed the identity of the isolates as T. dicentrarchi , with 16S rRNA and fusA gene sequencing clustering the isolates with the T. dicentrarchi type strain 35/09 T . Multiplex PCR‐based O‐AGC typing classified all 16 Chilean isolates as Type 1, which could aid in the development of an autogenous vaccine to prevent future tenacibaculosis outbreaks. RAPD analysis revealed clear genetic heterogeneity among all isolates, with a dominant genetic group comprising 11 isolates, regardless of the primer used. This study represents the first report of a bacterial disease in Palm ruff, expanding the list of endemic species susceptible to tenacibaculosis caused by T. dicentrarchi .

First insights into the proteome and antimicrobial properties of epidermal mucus from marine fish species of Chilean aquaculture diversification - Claudio A. Álvarez; María José Tapia; Belinda Vega; Fernando Albericio; Katherina Brokordt; Karina Farias; Marcia Oliva; Edison Serrano; Constanza Cárdenas; Eliandre de Oliveira; Fanny Guzman; Paula A. Santana (Fish & Shellfish Immunology, 2026)